2017
DOI: 10.1101/198101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The interface of malignant and immunologic clonal dynamics in high-grade serous ovarian cancer

Abstract: SummaryHigh-grade serous ovarian cancer exhibits extensive intratumoral heterogeneity coupled with widespread intraperitoneal disease. Despite this, metastatic spread of tumor clones is non-random, implying the existence of local microenvironmental factors that shape tumor progression. We interrogated the molecular interface between tumor-infiltrating lymphocytes (TIL) and cancer cells in 143 samples from 21 patients using whole-genome sequencing, immunohistochemistry, histologic image analysis, gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Consistent with this, we (Zhang et al, 2018) and others (Safonov et al, 2017) have reported negative associations between immune cell infiltration and intratumoral heterogeneity.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with this, we (Zhang et al, 2018) and others (Safonov et al, 2017) have reported negative associations between immune cell infiltration and intratumoral heterogeneity.…”
Section: Introductionsupporting
confidence: 93%
“…mRNA vs DNA). Given recent work from our group and others linking increased intratumoral heterogeneity with decreased immune cell infiltration (Safonov et al, 2017;Zhang et al, 2018), one could speculate that stemness might enable intratumoral heterogeneity by both increasing the replicative capacities of individual tumor clones and by shielding antigenic clones from elimination by the immune system.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Acquisition of 5 resistance may be related to specific mutational processes that drive genomic 6 heterogeneity [4,5] and clonal evolution [6,7]. HGSOC exhibits marked intra-site and 7 inter-site genetic heterogeneity across metastatic sites in the peritoneal cavity [5-7] with 8 altered immunological infiltrates and tumor microenvironments [8]. Detection of spatial or 9 temporal heterogeneity by multiple sampling in a single patient is expensive, invasive, and 10 often clinically impractical.…”
Section: Author Summarymentioning
confidence: 99%